Implementasi kurikulum merdeka belajar dalam novel cinta di dalam gelas karya Andrea Hirata - Kurniawan, Eva Dwi (Fakultas Sastra Universitas Negeri Malang, 2022)
The declaration of the Independent Learning curriculum emphasizes the collaborative aspect of many parties. It takes a lot of experience and freedom in learning in order to create mental qualities that are global in scale but still grounded in local values. Implementation of the learning curriculum can be seen in literary works. The novel Cinta di Dalam Gelas by Andrea Hirata has a similar pattern to the concept of the independent learning curriculum. This research focuses on the formulation of the problem of how the implementation of the independent learning curriculum is in the novel Cinta di Dalam Gelas by Andrea Hirata. The method used in this study uses the semiological theory proposed by Roland Barthes. The findings obtained are in the form of the implementation of a learning curriculum that refers to 1) freedom of learning, 2) collaboration, 3) being global, and 4) synergizing with the industrial world.